Strategi Petani dalam Menghadapi Fluktuasi Harga Kelapa di masa Pandemi Covid -19 (Studi Kasus di kelurahan Pulau Kijang Kecamatan Reteh Kabupaten Indragiri Hilir) - Yumita Marisa Usri; Sakdanur Nas; RM Riadi (Departement of Mathematics Education, 2023)
This research This study aims to determine Farmers' Strategies in Dealing with Fluctuations in Coconut Prices During the Covid-19 Pandemic. A Case Study in Kijang Island Village, Reteh District, Indragiri Hilir Regency. The method used in this research is descriptive research method by means of structured interviews and questionnaires with a quantitative approach. The results of the study show that the strength factor support is a rating of 19 and a score of 1,778. Identification of Weaknesses rating 27 and score 2.166. Identify Opportunity Factors with a rating of 11 and a score of 2.54. Identification of Threat Factors with a rating of 13 and a score of 1.789. Farmer empowerment is an effort to increase the potential and ability of farmers to increase productivity and efficiency in a sustainable manner. The goal is to provide motivation and training as well as generate public trust. Coconut processing is an opportunity for coconut farmers to develop their business and increase income